Peran Dinas Sosial Kota Mataram dalam Pemberdayaan Penyandang Disabilitas melalui Program Vokasi - Dony Jayeswara; Muhammad Mabrur Haslan; Ega Anzani (Mataram University, 2026)
Persons with disabilities in Mataram City face a gap between the ideal guarantee of vocational rights (Law No. 8 of 2016, Ministerial Regulation No. 7 of 2021) and the actual low rate of employment absorption, with only 47 individuals absorbed into the formal sector out of a work-ready adult population reaching 1,441 individuals. This study aims to analyze the role of the Mataram City Social Service in empowering persons with disabilities through vocational programs, as well as the factors that influence it. The research employs a qualitative descriptive approach, with subjects determined purposively and informants through snowball sampling, using interviews, observation, and documentation studies, analyzed using the Miles and Huberman interactive model, with validity tested through triangulation. The findings show that the Social Service has carried out its role across six indicators access and participation, training quality, skills improvement, job placement and entrepreneurship, support and facilitation, and collaboration and partnership although outcomes are more prominent in small-scale home-based entrepreneurship than in formal job placement. Internal factors (budget, human resources, facilities) and external factors (regulation, partnerships, social stigma) also influence the effectiveness of this role. The study concludes that the success of empowerment depends on the synergy between institutional capacity and the surrounding supportive ecosystem.